2018
DOI: 10.14411/eje.2018.029
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic pattern over centric fusion clinal variation in the water-hyacinth grasshopper, Cornops aquaticum (Orthoptera: Acrididae)

Abstract: The water-hyacinth grasshopper, Cornops aquaticum, occurs in the New World between latitudes 23°N, in Mexico, and 35°S in Central Argentina and Uruguay following the distribution of its host plants, i.e. different species of water-hyacinths (family Pontederiaceae) (Adis et al., 2007;Capello et al., 2010). The recent worldwide expansion of the water-hyacinth Eichhornia crassipes as a serious freshwater weed in tropical and subtropical, and even temperate, regions of the world (Center et al., 2002) has led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Although the strong negative association of fusion frequencies with maximum temperature, as well as the consistent repetition of clines along the Paraná and Uruguay River Basins, suggests an adaptive nature to the clinal variation in C. aquaticum populations (Colombo and Remis, 2018), it must be considered that clinal patterns can be also produced by neutral processes (Endler, 1973;Storz, 2002). For this reason, we have taken pains to perform additional analyses that further demonstrate a non-neutral explanation to the parallel clines, namely, a population pairwise differentiation study between the frequency of centric fusions and that of neutral microsatellite pattern.…”
Section: Phenotype Karyotype and Molecular Variation In C Aquaticum Populationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Although the strong negative association of fusion frequencies with maximum temperature, as well as the consistent repetition of clines along the Paraná and Uruguay River Basins, suggests an adaptive nature to the clinal variation in C. aquaticum populations (Colombo and Remis, 2018), it must be considered that clinal patterns can be also produced by neutral processes (Endler, 1973;Storz, 2002). For this reason, we have taken pains to perform additional analyses that further demonstrate a non-neutral explanation to the parallel clines, namely, a population pairwise differentiation study between the frequency of centric fusions and that of neutral microsatellite pattern.…”
Section: Phenotype Karyotype and Molecular Variation In C Aquaticum Populationsmentioning
confidence: 94%
“…Earlier studies in this region including populations located from 27 to 34°S latitude revealed that C. aquaticum has a rich chromosomal variability, with three polymorphic centric fusions whose frequencies increase from north to south (Colombo, 2008;Colombo and Remis, 2018). Even though the potential of polymorphic chromosomal inversions in facilitating local adaptation has been widely examined, just a few studies started to deal with the role of centric fusions in microevolution (Dumas and Britton-Davidian, 2002;Bidau et al, 2012;Colombo, 2013;Guerrero and Kirkpatrick, 2014;Wellband et al, 2018), which adds relevance to the results obtained in this study.…”
Section: Phenotype Karyotype and Molecular Variation In C Aquaticum Populationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Cornops aquaticum (Bruner 1906), another Neotropical grasshopper, also bears a system of polymorphic centric fusions that is second only to D. pratensis in complexness despite the relatively small area involved (Colombo 2007, 2008, 2009, Romero et al 2014, 2017, Colombo and Remis 2015, 2018, Colombo et al 2021). It is a semiaquatic grasshopper that lives, feeds, and lays eggs exclusively on floating plants of the family Pontederiaceae, or water-hyacinths, between latitudes 23° N (Southern Mexico) and 35° S (Central Argentine and Uruguay) (Adis et al 2007).…”
Section: Introductionmentioning
confidence: 99%